2015
DOI: 10.1111/1475-6773.12401
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmission Rates in U.S. States: Are Readmissions Higher Where More Patients with Multiple Chronic Conditions Cluster?

Abstract: Research Objective This study examines small area variations in readmission rates to assess whether higher readmission rate in an area is associated with higher clusters of patients with multiple chronic conditions. Study Design The study uses hospital discharge data of adult (18+) patients in 6 U.S. states for 2009 from the Healthcare Cost and Utilization Project of the Agency for Healthcare Research and Quality, linked to contextual and provider data from Health Resources and Services Administration. A multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…A chronic condition is a physical or mental health condition that lasts more than one year and causes functional restrictions or requires ongoing monitoring or treatment. 7 When a patient has more than one chronic condition-for example, diabetes, hypertension, and mood disorders-treatment can be difficult to manage. Treatment strategies or drug regimens may be similar-but can be very different-and one chronic condition may be better managed than the others.…”
Section: What Is a Chronic Condition?mentioning
confidence: 99%
“…A chronic condition is a physical or mental health condition that lasts more than one year and causes functional restrictions or requires ongoing monitoring or treatment. 7 When a patient has more than one chronic condition-for example, diabetes, hypertension, and mood disorders-treatment can be difficult to manage. Treatment strategies or drug regimens may be similar-but can be very different-and one chronic condition may be better managed than the others.…”
Section: What Is a Chronic Condition?mentioning
confidence: 99%
“…Patients with multiple chronic conditions (MCC) have two or more chronic illnesses at the same time. Using both patient and area level data, [1,2] past studies had found MCC to be a major driver of readmissions. Past studies also found readmission risks to be higher among elderly than nonelderly adults because of poorer health status and increased number of comorbidities.…”
Section: Chronic Conditions Include Both Physical and Behavioralmentioning
confidence: 99%
“…Past studies also found readmission risks to be higher among elderly than nonelderly adults because of poorer health status and increased number of comorbidities. [2] In this study, we particularly focus on a group of chronic con-ditions identified as subgroups of Ambulatory Care Sensitive Conditions (ACSCs), a well-used proxy measure for potentially preventable admissions that has been used in research, policy development and program design. These conditions are those that could exacerbate and lead to hospitalization if not prevented through better management in an ambulatory care setting.…”
Section: Chronic Conditions Include Both Physical and Behavioralmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalized readmission has been receiving growing attentions [1] because of its implications on cost and quality of care in the most recent decade. Professional experts in the field mostly believe a remarkable number of readmissions are truly preventable [2]- [5].…”
Section: Introductionmentioning
confidence: 99%